Systematic review and meta-analysis of the association between ABCA7 common variants and Alzheimer’s disease in non-Hispanic White and Asian cohorts - Liu, Da; Zhang, Hongwei; Liu, Cao; Liu, Jianyu; Liu, Yan; Bai, Na; Zhou, Qiang; Xu, Zhiyao; Li, Linyan; Liu, Hua (Frontiers in Aging Neuroscience, 2024)
Background and Aims: The relationship between ABCA7 gene and Alzheimer's disease (AD) has been widely studied across populations, however, the results are inconsistent. This study aimed to evaluate the association of ABCA7 gene with AD by the application of meta-analysis. Methods: Relevant studies were identified through comprehensive searches. The quality of each study was assessed using the Newcastle-Ottawa Scale (NOS). Allele and genotype frequencies were extracted from the included studies. The pooled Odds ratio with corresponding 95% confidence intervals was calculated using a random-effects or fixed-effects model. Multiple testing corrections were conducted using the false discovery rate method. The Cochran Q statistic and I2 metric were used to evaluate heterogeneity between studies, and Egger’s test and Funnel plot were employed to assess publication bias. Results: A total of 36 studies (21 polymorphisms, involving a total of 31,809 cases and 44,994 controls maximum) were identified and included in this meta-analysis. The NOS scores ranged from 7 to 9. Eleven SNPs (rs3764650, rs3752246, rs4147929, rs3752232, rs3752243, rs3764645, rs4147934, rs200538373, rs4147914, rs4147915, and rs115550680) in ABCA7 were significantly associated with AD risk, and two of these SNPs (rs3764650, rs3752246) were also found to be related to the late-onset AD (LOAD) subtype. In addition, two SNPs (rs4147929, rs4147934) were associated with the susceptibility to AD only in non-Hispanic Whites. Ten SNPs (rs3764647, rs3752229, rs3752237, rs4147932, rs113809142, rs3745842, rs3752239, rs4147918, rs74176364, and rs117187003) showed no significant relationship to AD risk. Sensitivity analyses confirmed the reliability of the original results. Deviation from Hardy-Weinberg equilibrium, ethnicity and individual studies may be the main sources of heterogeneity in combined analysis. Conclusion: Available evidence indicated that ABCA7 SNPs may be associated with AD risk. Future studies with larger sample sizes will be necessary to confirm the results.